FV 9 Deep Brain Stimulation for targeting tremor and ataxia in SCA 27. (May 2022) - Löffler, M.A.; Cebi, I.; Hormozi, M.; Synofzik, M.; Gharabaghi, A.; Weiss, D.
Abstract : Introduction: Spinocerebellar ataxia 27 (SCA 27) is a rare cerebellar ataxia caused by mutations in the FGF14 gene. It is characterised by tremor manifesting in early adulthood and slowly progressive ataxia in later decades. Here, we report the case of a 51 years old male patient who was initially diagnosed with medication-refractory essential tremor and therefore received thalamic deep brain stimulation (DBS). After the patient developed signs of cerebellar ataxia exome sequencing led to the diagnosis of SCA 27. In our clinical practice, we tested stimulation paradigms to target tremor and ataxia inspired by model findings (Anderson et al. 2019) suggesting differential effects of low- and high-frequency stimulation. Methods: The patient was implanted with quadripolar electrodes (model 3389, Medtronic) in the nucleus ventralis intermedius of the thalamus (VIM) with the lowest contact reaching the subthalamic fibre tracts. Initially, stimulation-induced manifestation of cerebellar ataxia was ruled out by a wash-out of DBS for 96 h. Next, we established a high-frequency (180 Hz) programme located at the thalamic contacts achieving best tremor control and a low-frequency (30 Hz) programme located at the lowest contacts to interfere with subthalamic fibre tracts. Electrode placement was verified using Lead-DBS. The Fahn-Tolosa-Marin Tremor Rating Scale (TRS) and the Scale of the Assessment and Rating of Ataxia (SARA) were performed for clinical assessment. At baseline, we evaluated the condition without stimulation (StimOFF) vs. 180 Hz vs. subthalamic 30 Hz stimulation. Further follow-up examinations were scheduled after 5 and 10 weeks. In the meantime, the patient activated the 180 Hz programme at daytime and either StimOff or 30 Hz stimulation at night. The investigator and patient were blinded to the night setting of the previous interval. Results: At baseline, tremor severity was attenuated by 180Hz DBS compared to StimOFF (TRS 13 vs. 21). Tremor was also attenuated by 30 Hz stimulation of the subthalamus at 1 mA (TRS: 14) but was gradually entrained with higher stimulation amplitudes up to 7 mA (TRS: 27). Changes of the SARA where mainly driven by the tremor component. During the first interval period, the patient adopted the 30 Hz night stimulation programme with 4 mA. In the follow-up examination tremor in the StimOFF condition (TRS: 12) improved to a TRS of 7 using the 180 Hz programme. Eventually, after the second period during which the patient adopted StimOFF at night, the baseline TRS was higher in the StimOFF condition (TRS: 23) and slightly improved to a TRS of 17 when using 180 Hz stimulation. Conclusions: Here, we report the first case of a patient with SCA 27 successfully treated with VIM-DBS in terms of tremor attenuation. We observed that low-frequency stimulation at night led to a more sustained tremor response by stimulation which may be due to antidromic stimulation of cerebellar-thalamic fibre tracts in the subthalamic area.